Linkage disequilibrium and population structure characterization in the cutting and racing lines of Quarter Horses bred in Brazil - Marchiori, Cíntia Maria [UNESP] (2019)
Different selection goals in the Quarter Horse breed have led to the formation of lines. These lines have different skills such as working with cattle or running and differ in morphology, physiology and inbreeding. The aim of this study was to characterize the linkage disequilibrium (LD, r2) in the cutting and racing lines of Quarter Horses bred in Brazil using large-scale SNP genotyping. Additionally, the effective population size (Ne) of the two populations (lines) was determined, as well as their structure and relationships. A total of 428 Quarter Horses (both sexes) of the two lines (cutting: 68; racing: 360), registered in the Stud book of the Brazilian Association of Quarter Horse Breeders (ABQM), were used. The animals had blood collected in the Sorocaba Jockey Club (Sorocaba/SP) and in dozens rural properties across the state of São Paulo, Brazil. In 2011, 188 horses (cutting: 68; racing: 120) were genotyped using a 54k SNP chip. The remaining animals (n = 240) were genotyped in 2015 using a 65k SNP chip. The average genomic r2 between marker pairs was 0.22 for the cutting line and 0.27 for the racing line. In the cutting line, the r2 was less than 0.20 between 100 and 150 kb, while the same threshold (0.20) was found between 300 and 350 kb in the racing line. The Ne was 60 and 50 effective animals in the last generation of the cutting and racing line, respectively. The greater extent of LD and smaller Ne in the racing line may be explained by the structure of the population, which is more closed because of the more rigorous registration process and greater influence of the Thoroughbred breed on the formation of this line. The results point to marked differences between the lines of this breed. In addition, subpopulations were found in the racing line, which may be related to the formation of families descending from important sires.